Sports involvement of girls and boys in basketball - Larissa Fernanda Porto Maciel; Vinícius Plentz de Oliveira; Jéssica Cozza; Larissa Cerignoni Benites; Viviane Preichardt Duek; Gelcemar Oliveira Farias; Alexandra Folle (Journal of Physical Education (Maringá), 2020)
The aim of this study was to analyze the sports involvement of girls and boys participating in the Basketball For All Program (Santa Catarina, Brazil). Eighty basketball practitioners attending the program participated in 2016. A questionnaire composed of closed questions was used, which was analyzed using descriptive (frequency and percentage) and inferential (chi-square, v-cramer, adjusted residuals) statistical resources. The results revealed an association between sex and the time of general sports practice, showing that girls had less experience in sports than boys. As for the weekly training frequency, it was found that the participants with lower weekly training hours were, therefore, those who trained less frequently (days) during the week. Boys with less time participating in the program and participating in sports initiation activities had lower weekly training frequency, while boys with longer experience and participating in competitive preparation activities trained more often during the week. It was concluded that the girls had less time to practice sports and that the organization of the program determines the weekly frequency of boys' involvement with basketball.